Specific Features of Management in Setting-Up and Developing Nich Organizations - S. Yu. Kazantseva (Plekhanov Russian University of Economics, 2021)
The article studies general and particular characteristics of two Russian companies functioning in the segment of organic food. The author analyzed companies ‘VkusVill’ and ‘EcoNiva’, one of them is a trade company and the other is an agro-industrial company, which lately is moving towards retail. Aspects dealing with cooperation of these companies were investigated. Special attention was paid to key stages of the companies’ development in order to show the sequence of steps during setting-up and developing operations being analyzed. The role of individual in developing business was demonstrated. These companies are characterized by the fact that their founders are strong and creative personalities, who have been executives since companies’ setting-up to the present moment. The author studied the stages of companies’ development in parallel with stages of professional and personality growth of their leaders. This article can be interesting for entrepreneurs, who plan to do business in the sphere of healthy food both as producers and retailers.